Reverse Trans-Sellar Neuroendoscopic Management of a Large Rathke’s Cleft Cyst Causing Obstructive Hydrocephalus: A Case Report - Lee, Han-Joo; Kwon, Hyon-Jo; Choi, Seung-Won; Kim, Seon-Hwan; Koh, Hyeon-Song; Youm, Jin-Young; Kim, Kyung Hwan (Brain tumor research and treatment, 2022)
Symptomatic Rathke's cleft cysts (RCCs) can be treated by surgical procedures, usually through an endonasal transsphenoidal corridor using either a microscope or an endoscope. We report a large suprasellar extended RCC causing obstructive hydrocephalus, which was efficiently managed by a novel surgical route named "reverse" trans-sellar approach using transventricular neuroendoscopy. A 48-year-old woman complained of persistent headache and a tendency to fall that had begun 6 months previously. The images obtained from MRI scan showed intra- and supra-sellar cystic masses occupying the third ventricle with obstruction of the foramina of Monro and the aqueduct of Sylvius. The cystic wall showed a slight enhancement, and the cystic contents showed iso-signal intensity on T1-and T2-weighted images. Instead of trans-nasal trans-sellar surgery, we decided to operate using a conventional transventricular endoscope. A thin cystic capsule, which blocked the foramina of Monro and the aqueduct of Sylvius, was fenestrated and removed and a third ventriculostomy was performed. The defect in the infundibulum between sellar and suprasellar cysts was widened and used as a corridor to drain cystic contents (reverse trans-sellar route). The final pathological finding revealed an RCC with focal metaplasia. We efficiently managed a large RCC by transventricular neuroendoscopic surgery with cyst fenestration and third ventriculostomy and simultaneously drained the sellar contents using a novel surgical route. Reverse trans-sellar neuroendoscopic surgery is a relevant treatment option for selective patients with large suprasellar extensions of RCCs.